The end of Irish history? : critical reflections on the Celtic tiger - Coulter, Colin, 1966-; Coleman, Steve, 1958- (Manchester University Press ; Distributed exclusively in the USA by Palgrave, 2003)
Ireland appears to be in the throes of a remarkable process of social and economic change. This text scrutinizes the interpretations and prescriptions that inform the deceptively simple metaphor of the "Celtic Tiger."